Can the Emotion Recognition Ability of Deaf Children be Enhanced? A Pilot Study - Dyck, Murray; Denver, E. (2003)
We evaluated the effectiveness of an 11-lesson psychoeducational program designed to enhance the ability of deaf children to understand the emotional experience of themselves and other people. The "Funny Faces Program" was provided to 14 children, aged 9 to 13, with moderate to profound hearing impairments. All children were enrolled in an "oral" education program at a school for the deaf. Alternate forms of the Emotion Recognition Scales (Dyck, Ferguson, & Shochet, 2001) were administered at pretest and posttest. Results indicate significant increases in emotion vocabulary and emotion comprehension but not in the speed or accuracy of emotion recognition (ER), from pretest to posttest. At posttest, children whose hearing loss was moderate to severe did not differ from hearing children in ER abilities but children with profound hearing loss continued to show substantial ability deficits.